Contouring Performance Study of a Fuzzy-based Practical Controller on an X-Y Table - Purtojo .; Heru S. B. Rochardjo; Gesang Nugroho; Herianto . (Proceeding of the Electrical Engineering Computer Science and Informatics, 2014)
This article presents a contouring performance of an improved practical fuzzy-based nominal characteristic trajectory following (NCTF) controller. The proposed fuzzy-based NCTF controller structure for continuous motion control is slightly different from the normal NCTF controller. It is composed of a nominal characteristic trajectory (NCT) and a fuzzy compensator designed using the practical design approach. Therefore, simple and easy of controller design are maintained. The NCT constructed through establishing procedure and the Mamdani type fuzzy compensator is designed according to the available information provided by NCT and the hardware specification. The contouring performance was evaluated by measuring the response of the system providing circle shape through simulation. The simulation result shows that the controller is promising as a practical controller for continuous motion.